Influence of the aftereffect of mineral fertilizers on the productivity of a long-term phytocenosis in the conditions of the Privilyui agrolandscape of the middle taiga subzone of Yakutia - N. V. Barashkova; V. V. Ustinova; A. I. Fedorova; L. K. Gabysheva (Аграрная наука Евро-Северо-Востока, 2022)
The article provides the research of 2011-2019 on studying the long-term influence of the aftereffect of 36-year application of mineral fertilizers on the productivity and nutritional value of long-term meadow phytocenoses. In a stationary experiment with a radical improvement of meadows, the following variants for applying mineral fertilizers were studied from 1974 to 2010: the minimum level was N62P60K11 (control), the average level was N202P175K43, and the maximum level was N318P362K189. In the conditions of the Privilyui agrolandscape of the middle taiga subzone of Yakutia, a long-term aftereffect of fertilizers (from 2011 to 2019) contributed to the preservation of the main dominant in the grass stand - couch grass (Elymus repens (L.) Nevski) up to 27.4-42.1 % and codominant – short-awned barley (Hordeum brevisubulatum (Trin) Link.) up to 14.7-24.3 %. During the aftereffect of fertilizers, the yield of cereal-forb phytocenosis averaged 1.71-2.03 t/ha of hay, which is 2.1-2.5 times higher than the yield of natural meadows. At the same time, hay forage contained up to 8.9-9.1 MJ of exchange energy, up to 0.62-0.65 feed units, and up to 80-90 g of digestible protein, which corresponds to the zootechnical norm.